Librarian-Faculty Collaboration for Literacy Courses: Promoting Better Learning for Preservice Teachers - Consalvo, Annamary; Doepker, Gina M.; Dubre, Vandry; Neel, Joanna (Language and Literacy / Langue et littératie, 2022)
This narrative describes a collaboration between three university literacy faculty and a subject librarian undertaken to embed library instruction across the semester in three required courses--children’s literature, early literacy, and disciplinary literacy--in order to help undergraduate preservice teachers better understand and incorporate children’s literature and high interest literature into their teaching. Concrete, scaffolded, hands-on experiences for preservice teachers with teaching materials helped to build awareness of foundational concepts in literacy instruction. Librarian/faculty collaborations have the potential to improve literacy teacher preparation programs by providing designed opportunities for active, concrete engagement coupled with structured reflection.